Southeast Asia Program Launch, Vietnam, May 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Images from the inauguration of the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS) Southeast Asia regional office in Vietnam. This included visits to national organisations currently undertaking innovative research, and farmers who are leading the way in efficient and productive farm management. The office will support the work of many contributing international and regional research and development partners as they work toward providing solutions to ensure climate-smart agriculture in the region. The program office is based at the <a href="http://www.irri.orgInternational Rice Research Institute (IRRI) in Hanoi, Vietnam.